Controlling fake veterinary drugs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
A senior veterinary research officer describes the need for regulation in the sales of veterinary drugs, to prevent sales of fake, out-or-date or adulterated drugs, and a recent initiative being undertaken in Nigeria to achieve this.